Viral dissemination and immune activation modulate antiretroviral drug levels in lymph nodes of SIV-infected rhesus macaques - Srinivasula, Sharat; Degrange, Paula; Perazzolo, Simone; Bonvillain, Andrew; Tobery, Amanda; Kaplan, Jacob; Jang, Hyukjin; Turnier, Refika; Davies, Michael; Cottrell, Mackenzie; Ho, Rodney J. Y.; Di Mascio, Michele (Frontiers in Immunology, 2023)
To understand the relationship between immunovirological factors and antiretroviral (ARV) drug levels in lymph nodes (LN) in HIV therapy, we analyzed drug levels in twenty-one SIV-infected rhesus macaques subcutaneously treated with daily tenofovir (TFV) and emtricitabine (FTC) for three months. The intracellular active drug-metabolite (IADM) levels (TFV-dp and FTC-tp) in lymph node mononuclear cells (LNMC) were significantly lower than in peripheral blood mononuclear cells (PBMC) (P≤0.005). Between Month 1 and Month 3, IADM levels increased in both LNMC (P≤0.001) and PBMC (P≤0.01), with a steeper increase in LNMC (P≤0.01). The viral dissemination in plasma, LN, and rectal tissue at ART initiation correlated negatively with IADM levels at Month 1. Physiologically-based pharmacokinetic model simulations suggest that, following subcutaneous ARV administration, ART-induced reduction of immune activation improves the formation of active drug-metabolites through modulation of kinase activity and/or through improved parent drug accessibility to LN cellular compartments. These observations have broad implications for drugs that need to phosphorylate to exert their pharmacological activity, especially in the settings of the pre-/post-exposure prophylaxis and efficacy of antiviral therapies targeting pathogenic viruses such as HIV or SARS-CoV-2 replicating in highly inflammatory anatomic compartments.